(3eKjQ GdZQGe Edi RjGQI GdbOS hGdTGes - (3CHh eMeO eMehO Hf ESeGYjd Hf eMehOs ((3CHh MGeO Hf Ndjd Hf jhSa s)
(3ChdgG (B:s
(3GdMeO ddg GdPi RGO eSLOfG GdCbUi TQakG HGdESQGA Edjg HNjQ GdHTQ CeG HYO agPG cJGH fajS GdNWQ Ldjd GdbOQ LGeY GdZQQ SejJg eKjQ GdZQGe ai RjGQI GdbOS hGdTGe GdaUd GdChd ai PcQ GdBjGJ GdhGQOI ai aVd GdbOS hGdTGe s
(3BNQgG (B:s
(3hbO JQcJ CTjGA ef GdaVGFd ai ChGFd eG jQhi Yf cYH GdCMHGQ hhgH Hf efHg hZjQgeG adjbQC GdeWGdY dg YjfkG hGdMeO ddg Ydi fYeg GdJi dG JMUi hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3cJHJ HQSe TjN GdESdGe TgGH GdOjf CHj GdYHGS CMeO Hf GdUdGM GdCehi GdeVQi GdebOSi GdTGaYi s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs